Internet as A Means of Modernization of Foreign Language Teaching - Toshmatovna, Nurmatova Guljahon; Malikovna, Artikova Nargiza (International Journal of Psychosocial Rehabilitation, 2020)
The modern child lives in the world of electronic culture. The role of the teacher is also changing — he should become a coordinator of the information flow. Therefore, the teacher needs to know modern techniques and new educational technologies to communicate in the same language with the child. In this regard, I believe that now every teacher should learn to use the world wide web in order to improve the content of education through the use of modern technologies.